DNA metabarcoding of orchid-derived products reveals widespread illegal orchid trade - Hugo J. De Boer (2018)
© 2017 The Author(s) Published by the Royal Society. All rights reserved. In eastern Mediterranean countries orchids continue to be collected from the wild for the production of salep, a beverage made of dried orchid tubers. In this study we used nrITS1 and nrITS2 DNA metabarcoding to identify orchid and other plant species present in 55 commercial salep products purchased in Iran, Turkey, Greece and Germany. Thirty samples yielded a total of 161 plant taxa, and 13 products (43%) contained orchid species and these belonged to 10 terrestrial species with tuberous roots. Another 70% contained the substitute ingredient Cyamopsis tetraganoloba (Guar). DNA metabarcoding using the barcoding markers nrITS1 and nrITS2 shows the potential of these markers and approach for identification of species used in salep products. The analysis of interspecific genetic distances between sequences of these markers for the most common salep orchid genera shows that species level identifications can be made with a high level of confidence. Understanding the species diversity and provenance of salep orchid tubers will enable the chain of commercialization of endangered species to be traced back to the harvesters and their natural habitats, and thus allow for targeted efforts to protect or sustainably use wild populations of these orchids.